Transparent and Low-Loss Luminescent Solar Concentrators Based on Self-Trapped Exciton Emission in Lead-Free Double Perovskite Nanocrystals - Zdražil, Lukáš; Kalytchuk, Sergii; Langer, Michal; Ahmad, Razi; Pospíšil, Jan; Zmeškal, Oldřich; Altomare, Marco; Osvet, Andres; Zboril, Radek; Schmuki, Patrik; Brabec, Christoph; Otyepka, Michal; et al. (ACS Applied Energy Materials, 2021)
Luminescent solar concentrators (LSCs) are light-harvesting devices that redirect solar light to an edge-attached photovoltaic cell, and thus, they have high potential to be incorporated directly into buildings’ windows to allow for generating electricity. Perovskite nanocrystals (PNCs) are promising materials for LSCs because their enticing optical properties can be engineered to provide a high photoluminescence (PL) quantum yield (QY) and low overlap between absorption and emission spectra. Replacement of toxic, lead-containing perovskites in LSCs by lead-free PNCs, while retaining high optical efficiency of the device, remains the key challenge, which needs to be overcome to build environmentally friendly solar-harvesting platforms. In this work, we use nanocrystals of Bi-doped Cs2Ag0.4Na0.6InCl6 double perovskites with a self-trapped exciton emission to realize for the first time a transparent, low-reabsorption, lead-free perovskite-based LSC. Fabricated 100 cm2 LSCs show an internal optical quantum efficiency of 21.2% with the corresponding internal concentration factor of 2.7. Monte Carlo (MC) ray-tracing simulations identified the loss caused by nonunity PL QY to be the most significant contribution to the overall efficiency loss. The MC simulations also allowed us to estimate the efficiency of 39.4% for 2,500 cm2 LSCs with hypothetical unity PL. These results demonstrate a significant promise held by Bi-doped lead-free PNCs for LSCs.
Keywords: photovoltaics; lead-free perovskites; double perovskites; perovskite nanocrystals; luminescent solar concentrators; Monte Carlo simulations